ANALISIS LEVEL KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS X BERDASARKAN GENDER DI SMK NEGERI 1 SOSORGADONG - Cici Eldina Marbun; Rahmatika Elindra; Sinar Depi Harahap (JURNAL MathEdu (Mathematic Education Journal), 2022)
Abstract This research is motivated by the fact that studying mathematics cannot be separated from various influencing factors, one of which is the student's gender (gender). The description of students' ability to understand mathematical concepts in mathematics learning in terms of gender is certainly an interesting focus and attention for educators. descriptive qualitative and informants in this study are students and teachers. The results of the research conducted can be concluded that the ability to understand mathematical concepts of students at SMK Negeri 1 Sosorgadong based on gender in the linear equation system material is included in the low criteria.